A comparative study of the effects of two alkanolamines on cement hydration. Issue 10 (13th May 2021) - Lu, Zichen; Kong, Xiangming; Jansen, Daniel; Zhang, Chaoyang
Abstract : The effects of two alkanolamines, triethanolamine (TEA) and diethanol-isopropanolamine (DEIPA), on cement hydration were comparatively investigated by several techniques including calorimetry, in situ X-ray diffraction analysis and pore solution analysis. Results show that the cement hydration regime is greatly altered by the alkanolamines, depending on their types and dosages. At the dosage of 0.5%, the aluminate reactions, including the formation of AFt and the reaction of C4 AF, are greatly accelerated, and consequently the silicate hydration is retarded. Compared to DEIPA, TEA increases the [Al] in pore solution, probably due to the stronger complexation with aluminate ions (Al(OH)4 − ), while DEIPA notably enhances the dissolution of C4 AF after depletion of gypsum, suggesting a stronger complexation with iron ions (Fe 3+ ). Through a comparison of the hydration of pure alite and cement systems, it is found that the effects of the two alkanolamines on cement hydration are primarily influenced by their impacts on the aluminate reaction.